Profile of Student Conceptions on the Direct Current Circuits with Multiple-Activity-Representation - Handhika, Jeffry; Alvarez, Joel Iglesia; Pramono, Nugroho Adi; Mayasari, Tantri; Mafudi, Innal (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
Difficulties in understanding concepts of Direct Current Circuits remain a persistent issue in physics learning, particularly in relating circuit construction, measurement, and conceptual reasoning. Therefore, this study aims to profile students’ conceptions of Direct Current (DC) circuits using the Multiple-Activity-Representation approach. This qualitative descriptive analysis research involved eight university students enrolled in the Fundamental Physics II course (2024/2025) at a university in Madiun. Students were asked to design, construct series, parallel, and combined circuits connected to a power supply, and measure current and voltage across each resistor. Data were collected through performance tasks, observations, and interviews, and analyzed through data reduction, categorization, and triangulation. Students’ conceptions were profiled into three categories: α, β, and γ. The findings reveal three distinct conception profiles. Students in category α were able to design and construct all types of closed circuits but demonstrated difficulties in conducting accurate measurements. Students in category β could design and construct series and parallel circuits but struggled with combined circuits and measurement processes. Students in category γ were able to design various circuit configurations conceptually but encountered difficulties in physically constructing combined circuits. These results indicate varying levels of conceptual and procedural understanding in DC circuits, particularly in integrating circuit representation, construction, and measurement. The study implies that the Multiple-Activity-Representation approach is useful for diagnosing the depth of students’ conceptions and identifying specific areas requiring instructional reinforcement, especially in experimental measurement and conceptual integration.